Mechanisms for achieving social security for the hearing impaired - fahmy, manel abed setar; ali abou hadid, fatma (Journal of Social Sciences and Humanities, 2021)
The study aims at identifying the reality of social security for people with special needs by determining the status of social status of people with hearing disabilities and determining in an attempt to reach a set of mechanisms that can contribute to achieving social security for people with special needs In general and persons with hearing disabilities in particular. This study belongs to the descriptive studies using the Comprehensive Social Survey for People with Hearing Disabilities in Al-Amal School for the Deaf and Mute of Girls in Dammam (35). The data of the field study were collected through the interview with the use of experts in sign language for easy communication with people with hearing disabilities , And the implementation of the open interview guide with experts in the field of caring for people with special needs of (5) academic and field experts.The study emphasized the importance of achieving social security for people with special needs and the importance of social integration. It pointed out that the level of "self-reliance" index, the social integration of the hearing impaired is average, while the level of "social status" and "employment opportunities for the hearing impaired" Study some of the mechanisms by which the social security of the hearing impaired can be enhanced.